A Survey on Role of Data Mining Techniques in Healthcare Domain: Exploring Data Mining Techniques in Healthcare (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In today’s world application of data mining in healthcare is growing faster as the health sector is rich in data and data mining has become a necessity. Healthcare organizations generate and collect large volumes of information to a daily basis. The healthcare environment is generally perceived as being ‘information rich’ however ‘knowledge poor’. Automated data mining and knowledge discovery techniques aid in fetching some interesting patterns. Data mining can enable healthcare organizations to anticipate trends in the patient's medical condition and behaviour proved by analysis of prospects different and by making connections between seemingly unrelated information. The raw data from healthcare organizations are voluminous and heterogeneous. It needs to be collected and stored in organized form and their integration allows the formation unite medical information system. Data mining in healthcare domain offers boundless opportunities for analyzing databases to discover patterns that are hidden in traditional data analysis techniques. These patterns can be used by healthcare practitioners to make predictions, perform diagnoses and set treatments for patients.In this survey paper we intend to study some of the data mining techniques such as classification, clustering, association, regression in healthcare field.